Identification of appropriate tools to gauge brain functions in a clinical setup of a developing country: A pilot study - Zafar, Umema; Habib, Syed Hamid; Raza, Syed Shahmeer (Pakistan Journal of Medical Sciences, 2023)
Objective: To identify the most appropriate tools to measure functions of the brain that can be utilized in the clinical setups of developing countries.Methods: This qualitative research with a three-step approach was carried out from January 2022 to May 2022 at the Institute of Basic Medical Sciences, Khyber Medical University, Pakistan. Firstly, literature was searched to identify main brain faculties, then interviews were conducted with regional field experts to identify appropriate scales for the selected functions. Lastly a rubric was filled using interview transcripts and literature.Results: The identified functions were vision, hearing, cognition, motor and emotions. Based on the rubric the best tests were visual fields (17/24), pure tone audiometry (16/24), Mini-Mental State Exam (20/24), Trait Emotional Intelligence Questionnaire (18/24), Romberg’s test (19/24) and Manual Muscle Testing (18/24).Conclusion: The clinicians in developing countries can utilize the visual fields, pure tone audiometry, Mini-Mental State Exam, Trait Emotional Intelligence Questionnaire, Romberg’s test and Manual Muscle Testing for most efficient, feasible, accurate and cost-effective measurement of brain functions.doi: https://doi.org/10.12669/pjms.39.6.7489How to cite this: Zafar U, Habib SH, Raza SS. Identification of appropriate tools to gauge brain functions in a clinical setup of a developing country: A pilot study. Pak J Med Sci. 2023;39(6):1840-1846. doi: https://doi.org/10.12669/pjms.39.6.7489This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.